HEMŞİRELİK ÖĞRENCİLERİNİN ÇOCUK İSTİSMARI VE İHMALİ FARKINDALIĞI İLE ÇOCUK HAKLARINA YÖNELİK TUTUMLARININ BELİRLENMESİ - Dertli, Semiha; Merter, Özlem Selime; Şengül, Zeynep Kisecik (Kırşehir Ahi Evran Üniversitesi, 2025)
Bu araştırmanın amacı, hemşirelik öğrencilerinin çocuk istismarı ve ihmali farkındalığı ile çocuk haklarına yönelik tutumları arasındaki ilişkinin belirlenmesidir. Araştırmanın evrenini, 01-20 Mart 2024 tarihleri arasında Türkiye’nin doğusundaki bir üniversitenin hemşirelik bölümünde eğitim-öğretim gören 167 öğrenci oluşturmuştur. Tanıtıcı Özellikler Formu, Çocuk İstismarı ve İhmali Farkındalık Ölçeği ve Çocuk Haklarına İlişkin Tutum Ölçeği online olarak veri toplamak için kullanılmıştır. Öğrencilerin Çocuk İstismarı ve İhmali Farkındalık Ölçeği ve Çocuk Haklarına İlişkin Tutum Ölçeği puan ortalamalarının sırasıyla 75.34±10.35, 89.73±11.54’tür. Araştırmada kadın öğrencilerin Çocuk İstismarı ve İhmali Farkındalık Ölçeği toplam puan ortalaması ile İhmal alt ölçek puan ortalamalarının ve Çocuk Haklarına İlişkin Tutum Ölçeği toplam puan ortalamasının daha yüksek olduğu; çocuk ihmal ve istismarını tanımada kendini yeterli hisseden öğrencilerin ölçek puan ortalamalarının daha yüksek olduğu belirlenmiştir (p

This study aimed to determine the relationship between nursing students’ awareness of child abuse and neglect and attitudes towards children’s rights. The study population covered 167 students from the nursing department of a university in eastern Turkey between 01 and 20 March 2024. A descriptive characteristics form, the Child Abuse and Neglect Awareness Scale, and the Attitudes Towards Children’s Rights Scale were used to collect data online. The students’ mean scores from the Child Abuse and Neglect Awareness Scale and Attitude Towards Children’s Rights Scale were 75.34±10.35 and 89.73±11.54, respectively. It was found that female students had higher mean scores on the total Child Abuse and Neglect Awareness Scale, the Neglect subscale, and the Attitudes Toward Children’s Rights Scale. Additionally, students who felt competent in recognizing child abuse and neglect had significantly higher mean scores on the Neglect subscale of the Child Abuse and Neglect Awareness Scale, and the difference was found to be statistically significant. A moderately significant positive correlation was found between the Child Abuse and Neglect Awareness Scale and the Attitude Towards Children’s Rights Scale mean scores (r=0.482, p
DETERMINING NURSING STUDENTS’ AWARENESS OF CHILD ABUSE AND NEGLECT AND THEIR ATTITUDES TOWARDS CHILDREN’S RIGHTS
Keywords: Pediatric Health and Illnesses Nursing; Çocuk Sağlığı ve Hastalıkları Hemşireliği